Liberalization of agricultural input markets in Bangladesh - Ahmed, Raisuddin; Haggblade, Steven (International Food Policy Research Institute, 2000)
As recommended by the Agricultural Commission of 1960, the East Pakistan Agricultural Development Corporation was established in 1963. Later known as the Bangladesh Agricultural Development Corporation (BADC), this public parastatal was responsible for procuring and distributing agricultural inputs such as fertilizers, seeds, agricultural equipment, and pesticides (Ahmed 1978a). BADC soon developed an elaborate national organization for delivering goods and services to farmers, establishing a virtual monopoly over fertilizer and agricultural equipment markets while conforming to government pricing and related policies. The corporation has since been replaced by liberalized and deregulated input markets. This chapter chronicles the process of liberalization, examines its impact, and draws lessons from the change.